Co-producing digitally-enabled courses that promote desistance in prison and probation settings. Issue 4 (2nd November 2018) - Morris, Jason; Knight, Victoria
Abstract : Purpose: The purpose of this paper is to set out an approach to innovation in criminal justice settings that gives service users a "voice" through the co-production of digital content designed for services that promote desistance. The authors describe the benefits and challenges of involving service users in co-creating mediated digital content within a co-production framework. Design/methodology/approach: This paper presents a new methodology for developing desistance-oriented programmes. The authors draw on a distinctive co-production exemplar within a prison setting that captures the perspectives of people who have shared their voices and the authors begin to explore the impact that co-production has had for them and for the service. Findings: The testimonies of service users involved in this exemplar provide insights into the benefits and challenges of co-production in the criminal justice system more broadly. Practical implications: Co-production is a credible service design strategy for developing digital services in prisons and probation; Complementary Digital Media (CDM) provides a promising pedagogical approach to promoting desistance; CDM enables service users to share their voice and stories to assist their peers. Digitally enabled courses to promote desistance can be well suited to peer support delivery models. Originality/value: CDM is a novel approach that uses co-production to create highly tailored content to promote desistance in discrete target groups. CDM can be used to digitalise processes within traditional offending behaviour programmes (OBPs). It can also enable the development of innovative toolkit approaches for flexible use within day-to-day therapeutic conversations between service users and criminal justice staff or peer supporters. CDM thereby offers practitioners in criminal justice settings an entirely new set of evidence-informed resources to engage service users.